New Directions in Anglo-Jewish History - Alderman, Geoffrey (Academic Studies Press, 2010)
The past two decades have witnessed a remarkable renaissance in the academic study of the history of the Jews in Great Britain and of their impact upon British history. In this volume Professor Geoffrey Alderman presents essays that reflect the richness of this renaissance, penned by a new generation of British and American scholars who are uninhibited by the considerations of communal image and public obligation that once exercised a powerful influence on Anglo-Jewish historiography. History does not have lessons, says Alderman, but it may provide signposts, and he adds that in the case of the essays presented here "I believe there is one signpost that we would all do well to ponder: in multicultural Britain hard-working immigrants may be welcome, or they may be feared – or both. They are destined to remain not quite British, and, for better or worse, they are destined to bequeath this otherness to the generations that follow them."